Replacement of soybean oil by Hermetia illucens fat in turkey nutrition: effect on performance, digestibility, microbial community, immune and physiological status and final product quality. Issue 3 (3rd May 2020) - Sypniewski, J.; Kierończyk, B.; Benzertiha, A.; Mikołajczak, Z.; Pruszyńska-Oszmałek, E.; Kołodziejski, P.; Sassek, M.; Rawski, M.; Czekała, W.; Józefiak, D.
ABSTRACT: 1. The aim of the present study was to investigate the effect of partial (50%) or total replacement of soybean oil (SO) by black soldier fly larvae (BSFL) fat on the growth performance, coefficients of apparent nutrient digestibility, selected internal organ weights and length, pancreatic enzyme activity and gastrointestinal tract (GIT) microecology modulation, as well as microbiota activity, physiological and immunological responses in young turkey poults. 2. A total of 216, seven day old female turkeys (B.U.T 6) were randomly distributed to three dietary treatments using six replicate pens per group with 12 birds per pen. The following design of the trial was applied: SO 100% soybean oil; BSFL50 a 50/50 combination of SO and BSFL fat; or 100% BSFL fat (total replacement of SO). 3. The use of BSFL fat did not affect the growth performance, nutrient digestibility, GIT morphology, or quality of the breast and thigh muscles. However, reduced trypsin activity was noticed in the BSFL100 group, but this had no effect on digestibility. Total replacement of SO reduced proliferation of potentially pathogenic bacteria, i.e., Enterobacteriaceae spp., as well as decreasing levels of IL-6, while partial substitution lowered the TNF-α concentration. 4. The replacement of commonly used SO by BSFL fat can be successfully applied in young turkey poult nutrition. BSFL fat may be considered an antimicrobial agent and support immune responses.